A5.8 The use of cardiovascular risk module within the swedish rheumatology quality registry (SRQ) helps in daily clinical praxis. (13th February 2015) - Kvarnström, M; Antovic, A; Turesson, C; Ljung, L; Södergren, A; Leonard, D; Henrohn, D; Dehlin, M; Wållberg-Jonsson, S; Svenungsson, E
Abstract : Background and objectives: Patients with inflammatory rheumatic diseases suffer from increased morbidity and mortality in cardiovascular disease (CVD). The increased risk for CVD is related to disease activity and duration and to concomitant presence of traditional cardiovascular risk factors. The working group within the Swedish Society for Rheumatology (SRF) has developed Guidelines for cardiovascular primary prevention in patients with inflammatory rheumatic diseases, approved by the Swedish Rheumatology Association in 2009. In order to facilitate their use in clinical praxis, we have introduced an electronic aid, a cardiovascular risk module, within the widely used Swedish Rheumatology Quality Registry (SRQ). Material and methods: The module represents a modification of the Heart SCORE, requiring age, gender, smoking status, systolic blood pressure and total cholesterol to be completed. Additionally information about the following items is registered: Family history, obesity, levels of LDL/HDL, fasting glucose, impaired renal function, previous manifestations of CVD and persistent systemic inflammation (physicians' estimation). The final algorithm assumes, based on previous studies, that the risk for CVD in patients with rheumatoid arthritis (RA) and persistent inflammation and/or severe extra-articular manifestations, and in patients with systemic lupus erythematosus (SLE) is equal to the CVD risk in diabetic patients. These patients are thus handled as "higher CVD risk" in the module. Results: The calculated 10-year mortality risk for a myocardial infarction is expressed in percent (%), considering a risk ≥ 5% as high. Treatment recommendations, e.g. individualised lifestyle advice, are given to all patients. Special units at outpatient's clinics are formed, including health professionals working with lifestyle counselling. General targets are <140/90mmHg for blood pressure and <5mmoL/L for cholesterol, with lower targets for high risk patients. Prolonged treatment and higher dosages of NSAIDS are considered as potential CVD risk factors and should therefore be reevaluated. If presence of antiphospholipid antibodies, the physician is advised to consider treatment. Optimal treatment of the rheumatic disease is a primary goal, which is also beneficial for the vasculature. The cardiovascular module has been used at Rheumatology Clinics in Swedish hospitals during the last 3 years. In totally, 624 registrations comprising 455 patients are completed until October 2014. Conclusions: The cardiovascular module within Swedish Rheumatology Quality Registry is a time-saving and convenient tool which helps us to actively implement CVD prevention in daily clinical praxis. Further evaluations and, if needed, modifications of the module are planned. We hope to include all patients with newly diagnosed RA at several collaborating University hospitals in Sweden in 2015.